Helpful factors of group cognitive behavioral therapy in overweight and obese college students - Zhao, Zixian; Zhang, Yuting; Zhao, Dan (Frontiers in Psychology, 2025)
ObjectiveTo explore the helpful factors of group cognitive behavioral therapy in overweight and obese college students.MethodsTwelve overweight and obese college students were selected to receive group cognitive behavioral therapy, and semi-structured interviews were conducted to gather insights on their perceived helpful factors during the intervention, and thematic analysis was employed to process the interview data.ResultsThe cognitive-behavioral weight loss group intervention had three categories of helpful factors: (1) “Cognitive Adjustment and Skill Learning,” including thought recognition and transformation, emotional experience and acceptance, motor learning and practice, dietary adjustments and changes, and knowledge assimilation and experimentation. (2) “Group process and motivational factors,” including a sense of belonging and cohesion, information transfer and facilitation, and a sense of self-efficacy. (3) “Gains and overall results,” including healthy living and weight loss, renewed hope, and a positive mindset.ConclusionGroup cognitive behavioral therapy achieves group weight loss through the synergistic effects of multiple factors.